Respuesta :

Answer:

[tex](8 * 10^{-4}) * 0.08[/tex] = [tex]64 * 10^{-6}[/tex] = [tex]\frac{64}{10^6}[/tex] = [tex]\frac{64}{1000000}[/tex] = [tex]0.000064[/tex]

Step-by-step explanation:

Given

[tex](8 * 10^{-4}) * 0.08[/tex]

Required

Simplify

[tex](8 * 10^{-4}) * 0.08[/tex]

Express 0.08 as standard form

[tex](8 * 10^{-4}) * 8 * 10^{-2}[/tex]

Remove bracket

[tex]8 * 10^{-4} * 8 * 10^{-2}[/tex]

Apply commutative property:

[tex]8* 8 * 10^{-4} * 10^{-2}[/tex]

[tex]64 * 10^{-4} * 10^{-2}[/tex]

Apply law of indices

[tex]64 * 10^{-4-2}[/tex]

[tex]64 * 10^{-6}[/tex]

Solving further:  Express [tex]10^{-6}[/tex] as fraction by applying law of indices

[tex]64 * \frac{1}{10^6}[/tex]

[tex]\frac{64}{10^6}[/tex]

[tex]10^6 = 1000000[/tex]

So, we have:

[tex]\frac{64}{1000000}[/tex]

Lastly:

[tex]0.000064[/tex]

Hence:

[tex](8 * 10^{-4}) * 0.08[/tex] = [tex]64 * 10^{-6}[/tex] = [tex]\frac{64}{10^6}[/tex] = [tex]\frac{64}{1000000}[/tex] = [tex]0.000064[/tex]

ACCESS MORE